2012
DOI: 10.1177/0734904112453566
|View full text |Cite
|
Sign up to set email alerts
|

Global modelling of fire protection performance of an intumescent coating under different furnace fire conditions

Abstract: This article presents a method to model the overall fire protection performance of an intumescent coating under different post-flashover furnace fire conditions. Intumescent coatings are reactive fire protection materials, and their fire protection performance, among which the maximum expansion ratio is the key indicator, depends on the heating condition. The aim of this research is to find one common set of properties to enable the intumescent coating fire protection performance to be predicted across differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 15 publications
5
84
1
1
Order By: Relevance
“…That is why there is a need for a detailed understanding of the transient heat transfer properties of an expanding char and predictive tools to aid product development by reducing the number of experimental tests needed. Whereas the performance of an inert insulating coating is relatively well understood and quantifiable [44], a dynamically expanding char, for which the ultimate insulation properties depend on the heating regime, is complicated and the proposed models based on static insulators are not comprehensive enough to permit accurate predictions [45][46][47][48].…”
Section: Modeling and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why there is a need for a detailed understanding of the transient heat transfer properties of an expanding char and predictive tools to aid product development by reducing the number of experimental tests needed. Whereas the performance of an inert insulating coating is relatively well understood and quantifiable [44], a dynamically expanding char, for which the ultimate insulation properties depend on the heating regime, is complicated and the proposed models based on static insulators are not comprehensive enough to permit accurate predictions [45][46][47][48].…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…The model involves the swelling through the physical parameters of the intumescent coating and they found an acceptable agreement between the simulation and the experience in different fire and explosion scenarios (BLEVE, Boiling Liquid Expanding Vapor Explosion). Zhang et al reported an approach to allow the intumescent coating expanding process to be accurately predicted for different heating conditions [47,48]. The expansion of the intumescent coating was predicted through the introduction of a trapped gas that is a function of the local temperature and rate of mass reduction ratio (it was reasonably assumed that only trapped gases participats in the expansion process).…”
Section: Figurementioning
confidence: 99%
“…Unlike conventional fire protection materials, intumescent coatings release gases, and the gases caused the coatings to expand at high temperatures. The heating condition has an effect on the expansion process and then on the fire protection performance of intumescent coating . At present, building fire resistance design is largely based on standard fire condition; therefore, comparisons of the fire protection performance of intumescent coatings between the standard and nonstandard fire conditions are necessary for determining whether the insulative properties obtained from standard fire tests could be used to assess the performance of intumescent coatings in various fire scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The research that is most relevant to the current work comes from that of Zhang et al and Zhang et al where they attempted to predict the expansion process of intumescent coatings. In their model, they assume that the expansion ratio of intumescent coatings is directly proportional to the ratio of density of the solid blowing agent to the released gas density, assuming that the intumescent coating pressure is maintained at the atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They then proposed a hypothetic link between the amount of trapped gas, as a proportion of the total gas released, and the temperature and heating rate. They have compared their predictions against their own cone calorimeter Zhang et al and furnace fire Zhang et al tests. Although their comparisons show good agreement between their model prediction and test results, their assumption that most of the released gas escapes from the intumescent coating during the expansion process is highly questionable because this would require the released gas from inside the intumescent melt to travel through the coating and further to the outside air almost instantly when they are released.…”
Section: Introductionmentioning
confidence: 99%